Kubord 2: Word relations Dagens Nyheter 2022 - Språkbanken Text (University of Gothenburg, 2024)
Kubord 2 is an updated version of Kubord and contains both token frequencies and word relations from modern newspaper texts from the The National Library of Sweden.

Kubord 2 är en uppdaterad version av Kubord och innehåller utöver ordfrekvenser även ordrelationer från moderna tidningstexter från Kungliga biblioteket.
Kubord 2: Ordrelationer Dagens Nyheter 2022
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik